HIV Infection of Male in Pekanbaru in 2018 - Delfiria, S; Muhaimin, T; ., Nurlisis; Yunita, J; Purnawati Rahayu, E (KnE Life Sciences, 2019)
The case of HIV and AIDS in Pekanbaru in 2017 is 448 cases, this HIV-AIDS case is dominated by male gender, with each HIV is 66% and AIDS is 76%. The identification toward the infection risk factor of HIV-AIDS in some region become the basis of strategy determination and the policy of HIV-AIDS prevention in this region, which can be utilized well by the stakeholder or health service. The purpose of this research is to find out the infection risk factor of HIV in male in Pekanbaru with case control design. The research sample was taken to male which had Voluntary Counseling Testing in clinical service of VCT in the nearby Health Center in Pekanbaru with the total sample of 201 people, it was consist of 67 people’s case and the control of 134 people. The result of the research shows that the risk factors which are related to the HIV infection of male in Pekanbaru are the usage of condom (OR = 3,041), condom usage consistency (OR = 7,010), couple switch (OR = 2,591), couple switch more than two (OR = 3,661), doing anal sex (OR= 6,486) and doing anal sex with condom (OR =16,923). Anal sex using condom also become the dominant risk factorof HIV infection of male Pekanbaru in 2018, with the OR value of 16,923 which means doing anal sex without condom is 17 times risk higher to get infected by HIV thandoing anal sex with condom. These risk factors give the 68% supports of HIV infection of men in Pekanbaru in 2018. Keywords: HIV infection, infection risk factor of HIV, male, Pekanbaru